Methylene blue degradation over M-TiO2 photocatalysts (M= Au or Pt) / Degradación de azul de metileno sobre fotocatalizadores M-TiO2 (M = Au o Pt) - MURCIA MESA, JULIE JOSEANE; Guarín Romero, Jhonatan Ricardo; Cely Macías, Ángela Carolina; Rojas Sarmiento, Hugo Alfonso; Cubillos Lobo, Jairo Antonio; Navío Santos, José Antonio; Hidalgo López, María del Carmen (Universidad Pedagógica y Tecnológica de Colombia, 2017)
AbstractIn this study it was evaluated the methylene blue degradation over TiO2 modified by sulfation and Au or Pt addition. These materials were synthesized by photodeposition method and they were widely characterized by different techniques. In general, it was found that Au or Pt particles size distribution can be effectively controlled modifying the deposition time. It was also found that metal particle size and dye adsorption on TiO2 surface, are important factors influencing the methylene blue degradation rate.  The highest dye degradation was obtained on Au-TiO2 photocatalyst prepared by using 120 min of deposition time, the highest effectiveness of this material in the methylene blue degradation can be mainly due to a combined effect between the presence of gold nanoparticles acting as a sink for the electrons photogenerated during the catalytic reaction and the better adsorption of the dye over the TiO2 surface partially covered by gold particles with the largest sizes.